Darwin : an exceptional voyage - Grolleau, Fabien, 1972-; Royer, Jérémie, 1979-; Vick, Serafina (2019)
"When the young amateur naturalist Charles Darwin boarded the HMS Beagle in 1831, he had no idea what lay in store on his five-year voyage across the world. Darwin was disenchanted, moved, scandalised and awestruck by the vast discoveries that he made on his journey. On his return, he wrote his famous and controversial theory on the evolution of species. This long, perilous exploration was a journey that changed a man, and in doing so, the course of science itself."́--
First leg: England, Cape Verde, Brazil -- Second leg: Brazil, Argentina, Uruguay, Patagonia -- Third leg: Patagonia, Tierra del Feugo, Chile -- Fourth leg: Chile, Galápagos, Pacific -- Fifth leg: Pacific, Oceania, Cocos Island, South Africa, England.
Originally published in French as: HMS Beagle, aux origines de Darwin (Dargaud, ©2016 [i.e. 2018]).
Keywords: Darwin, Charles, -- 1809-1882 -- Travel -- Comic books, strips, etc; Darwin, Charles, -- 1809-1882.; Evolution (Biology) -- History -- Comic books, strips, etc; Naturalists -- Great Britain -- Biography -- Comic books, strips, etc; Scientific expeditions -- History -- 19th century -- Comic books, strips, etc; Voyages around the world -- History -- 19th century -- Comic books, strips, etc; Graphic books; Comic books, strips, etc; Comics (Graphic works); Biographical comics; Nonfiction comics; Graphic novels